Handbook of research on emerging technologies for effective project management - Jamil, George Leal, 1959-; Malheiro, Armando, 1957-; Lopes, Sérgio Maravilhas (IGI Global, 2020)
"This book explore the relationship between project management principles and methods under the phenomena of emerging technologies introduction"--